PENERAPAN MODEL PEMBELAJARAN ROUND TABLE UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI BERBANTUAN MEDIA GAMBAR SERI DI SEKOLAH DASAR - Azzahra; Iis Aprinawati; Mufarizuddin; Muhammad Syahrul Rizal; Fadhilaturrahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study originated from the low level of students' narrative essay writing skills in Indonesian language subjects at SDN 011 Langgini. One of the efforts made to overcome this problem is by applying the Round Table learning model.The purpose of this study is to describe the application of the Round Table learning model to improve narrative essay writing skills with the help of serial picture media.This study used the Classroom Action Research (PTK) method which was carried out in two cycles. Each cycle consisted of two meetings and went through four stages, namely planning, implementation, observation, and reflection.The subjects in this study were class IV students totaling 15 people, consisting of 12 male students and 3 female students. Data collection techniques include observation, tests and documentation.Based on the results of the study, it can be concluded that the skill of writing narrative essays through the Round Table learning model for fourth grade students of SDN 011 Langgini has increased. In cycle I, the average student score reached 66.6 with a percentage of classical completeness of 60%. Meanwhile, in cycle II, the average score increased to 83.4 with classical learning completeness reaching 86.6%. Thus, the application of the Round Table learning model was proven to be able to improve the narrative essay writing skills of grade IV students at SDN 011 Langgini.